Eagle Nesting Groups in the Important Bird Area “Donyz-Tau cliff faces” in 2022 - Ilya E. Smelansky; Andrey A. Tomilenko; Anna N. Barashkova; Roman N. Alexandrovich (Пернатые хищники и их охрана)
The Important Bird Area (IBA) “Donyz-Tau cliff faces” (KZ019), with an area of 387,110 hectares, has been allocated by I.V. Karyakin (2008) based on survey results in 2003–2006. Survey showed several globally threatened and biome-specific species nesting here, including Steppe Eagle (Aquila nipalensis) and Eastern Imperial Eagle (Aquila heliaca), 26 breeding pairs of each species (Karyakin, 2008). Condition of large raptor nesting groups in the IBA was then checked (territories were always checked partially) in 2012, 2017, and 2018. IBA “Donyz-Tau cliff faces” is located in the Aktobe, Atyrau, and Mangistau regions of Kazakhstan, with 70% of an area belonging to Aktobe region.